Reducing Surgical Site Infection by Placing Subcutaneous Drain in the Obese Patients - S, Dehkhoda; Pour, N Arian; Roozegar, R (Journal of Diseases, 2017)
In this study the effect of placing subcutaneous drain in the incision site of obese patients undergoing bariatric surgery, on the rate of incision site infection was evaluated. 200 obese patients of both sexes included in the study on the basis of the inclusion and exclusion criteria. They were divided into two groups on the basis of their accessibility. For patients belonging to group II (study cases), subcutaneous drain was placed at the incision site. Follow up of the patients shows subcutaneous drain placed at the incision site reduces the rate of infection up to 2% which is significantly lower than the infection rate among patients for whom drain was not placed (P<.05). In spite of emphasis to use sutures, drains and foreign bodies only with adequate indications to avoid surgical site infection and based on the merits of employing drain in evacuating the collected material to prevent infection, we recommend the use of subcutaneous drains in obese patients as incision infection may lead to longer hospitalization or readmission. As higher treatment expenditures and higher mortality rate are the consequences of infection, every effort to reduce the consequences rates following bariatric surgery in obese patients is valuable and advisable.